Comparative analysis of community perceptions on socioeconomic impacts of Tun Sakaran Marine Park, Malaysia - Azmi bin Abd. Majad; Lim Thien Sang; Kasim Bin Hj. Md. Mansur; Agnes Paulus Jidwin (2018)
The study aims to investigate the perceptions of the local community of Semporna with regard to the establishment of the Tun Sakaran Marina Park. Specifically, the present paper compares the opinions on socioeconomic impacts of its establishment of two community groups: ocean-dependent community versus all the others. Structured questionnaire was used and purposive-sampling method was carried out. More than 200 respondents participated and data were analyzed using SPSS. The results generally indicated the local community had benefited socioeconomically from the marine protected areas. They were feeling proud of having the park. Despite recorded mostly favourable perceptions, significant opinion differences in certain aspects were observed between the two groups. An important aspect of concern was job opportunity, where the ocean-dependent group felt there was not much job opportunity. On the contrary, the rest of the local community thought differently as they generally agreed employment opportunity was good. Significant gap was also recorded in term of activities that can be done in Semporna, in which the former was showing a lower degree of optimism. These results seemed to suggest there may be disparities in term of economic opportunity or resource distribution among the community in Semporna, which may explain a much lower self-reported monthly income of the ocean-dependent community group. In terms of marine conservation and preservation, the ocean-dependent community also expressed stronger perceptions on ineffectiveness. Moving forward, the paper recommended some suggestions to narrow the opinion gaps between the two community groups.